Innovative Methods for Treating Uterine Fibroids - Fozilovna, Axtamova Ozoda (Journal of Science in Medicine and Life, 2024)
Uterine fibroids are a diagnosis that scares any woman. Such a decision of an ultrasound diagnostic doctor can make even the most resilient women panic. However, you should not suddenly worry about the risk of fibroids. First, during the next menstrual cycle, it is necessary to contact another specialist and repeat the ultrasound examination (UZI). What is uterine myoma, why does it appear, myoma treatment with conservative and surgical methods and what are its symptoms? We will dwell on this in detail.